Persepsi Mahasiswa Pendidikan Bahasa Arab Terhadap Politik Identitas Islam Dalam Pemilihan Umum 2024 - Dwi Wulan Sari; Maksudin Maksudin; Sibawaihi Sibawaihi; Aulia Mutiara Putri (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Islamic identity politics is often used as a means of struggle used by a group to support the campaign period. Not a few end up choosing leaders because of the doctrine of religious equality. Students in identity politics have a big role and participation in carrying out the struggle to help resolve cases of intolerance and discrimination that occur. This study uses a qualitative method. Based on the research results, it can be understood that the existence of Islamic identity politics in general elections will have the potential to create conflict and division in society. If Islamic identity politics is allowed to grow and develop in the daily lives of community groups and bring down one another, then the big impact can damage diversity. The general election is a good opportunity for all Indonesian people, especially for students. It is not only the election of wise leaders, but the success of democracy is the hope to look forward to. This role is not only borne by students, but also for all Indonesian people. The importance of cooperation in creating the perception and implementation of politics that is free from group interests and realizing quality general elections.